Edible insects: Tendency or necessity (a review). Issue 1 (31st December 2022) - Papastavropoulou, Konstantina; Xiao, Jianbo; Proestos, Charalampos
Abstract: Eating insects has been a widespread habit in many cultures for many years. Edible insects represent an innovative food source with many advantages that will help the problem of protein and energy shortages created by the rapid growth of the world population. Using insects as food can increase the economy and help protect the environment and the human survival. Their nutritional value is excellent, since according to many studies insects have high protein content, high concentrations of various essential amino acids, a well‐balanced fatty acid profile, with a high content of monounsaturated, polyunsaturated fatty acids and many minerals, trace elements, and vitamins. However, there are several risks in the use of edible insects, which need to be researched more extensively. Main goals are to spread knowledge and change the process of obtaining edible insects in better and safer ways. So that the edible insect food industry can develop on a solid basis, through the expansion of the composition of the insects already used and the future legalization of new species of edible insects as well as the establishment of additional legislative frameworks for the breeding, development, processing, storage, and safety of these innovative new foods. Abstract : Edible insects represent an innovative food protein and bioactive compounds source with many advantages that will help the problem of rapid growth of the world population